Capturing chaotic chromosomes: Pairing in action - Bertucci, Micka C. (2018)
Accurate chromosome segregation is critical for the formation of haploid gametes, and therefore healthy offspring. Errors in segregation result in aneuploidy, which increases exponentially with maternal age (Hassold and Hunt, 2001). Maternally aged mouse oocytes were recently found to exhibit premature sister chromatid separation due to reduced levels of Securin, an essential regulator of sister chromatid cohesion (Nabti et al, 2017). This landmark finding was facilitated by using chromosome spreads that allow for the visualization of meiotic processes, such as recombination, synapsis, crossing over, and cohesion. This powerful technique is easy to perform and analyze, and allows for the identification of markers for different processes, including DNA damage and repair.